CO luminosity–FWHM correlation of low- and high-redshift galaxies and its possible cosmological utilization. Issue 4 (10th January 2019) - Wu, Yi-Han; Goto, Tomotsugu; Kilerci-Eser, Ece; Hashimoto, Tetsuya; Kim, Seong-Jin; Chiang, Chia-Ying; Huang, Ting-Chi
ABSTRACT: A linear correlation has been proposed between the CO luminosity (L^′ _CO ) and the full width at half-maximum (FWHM) for high-redshift (z > 1) submillimetre galaxies. However, the controversy concerning theL^′ _CO –FWHM correlation seems to have been caused by the use of heterogeneous samples (e.g. different transition lines) and/or data with large measurement uncertainties. In order to avoid the uncertainty caused by using different rotational transitions, in this work we make an extensive effort to select only CO( J = 1−0) data from the literature. We separate these wide-ranging redshift data into two samples: the low-redshift (z < 1) and high-redshift (z > 1) samples. The samples are corrected for lensing magnification factors if gravitational-lensing effects appeared in the observations. The correlation analysis shows that there exists significantL^′ _CO –FWHM correlations for both low-redshift and high-redshift samples. A comparison of the low- and high-redshiftL^′ _CO –FWHM correlations does not show strong evolution with redshift. Assuming that there is no evolution, we can use this relation to determine the model-independent distances of high-redshift galaxies. We then constrain cosmological models with the calibrated high-redshift CO data and the sample of Type Ia supernovae in the Union 2.1 compilation. In the constraint forw CDM with our samples, the derived values arew 0 = −1.02 ± 0.17, Ωm0 = 0.30 ± 0.02 andH_0=70.00± 0.60 km s^-1 Mpc^-1 .